PROBLEMS OF ACCOUNTING AND EVALUATION OF INTANGIBLE ASSETS IN THE CONDITIONS OF DIGITALIZATION - I.V OSIPOVA; Y.S PIPIYA (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
Currently, one of the priority, effective areas of economic development in most countries of the world is due to the large-scale appearance of digital technologies and products of the digital economy of a new generation. The development of digital technologies, the creation of products, services of the digital economy refers to objects of intellectual property (OIP), intangible assets (IA). Their development, development and use leads to an inevitable transformation of the models of any financial and economic activity. In the modern construction industry, more than a dozen innovative technologies, materials, techniques, and methods are currently used, which makes this industry effective and competitive, but there are also problems associated with the accounting and assessment of digitalization objects.OIP includes business reputation or goodwill. Digital technologies can seriously affect the business reputation of companies (organizations, enterprises), their investment attractiveness. However, accounting does not always meet modern requirements for assessing created and intended for the implementation of digital technologies, which can reduce the investment attractiveness of companies, their competitive advantages and reduce protection against unfair competition in domestic and foreign markets. This article is devoted to the analysis of the problems and shortcomings of the legal regulation of accounting and evaluation of digitalization objects